2021
DOI: 10.1039/d1ra05301a
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between structural deformations and flat band phenomenology in twisted bilayer antimonene

Abstract: Strong interlayer interactions allows for electron localization and emergence of flat bands in relatively higher twist angles in Sb bilayer. Noncovalent functionalization with electron acceptor molecules may modulate their energy position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…states, [12,13] and flat bands. [14,15] Few-layers antimonene is also predicted to exhibit fruitful strain effects, such as a band gap modulation induced by inter-layer compression, [11] and the quantum spin Hall state induced by in-plane strain. [16][17][18] Thus, spiral antimonene is a proper candidate for studying the strain effects on spirals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…states, [12,13] and flat bands. [14,15] Few-layers antimonene is also predicted to exhibit fruitful strain effects, such as a band gap modulation induced by inter-layer compression, [11] and the quantum spin Hall state induced by in-plane strain. [16][17][18] Thus, spiral antimonene is a proper candidate for studying the strain effects on spirals.…”
Section: Introductionmentioning
confidence: 99%
“…Two‐dimensional (2D) van der Waals (vdW) layered materials are widely studied in the past two decades. [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ] These materials are vdW stackings of atomic layers of 2D covalently bonded materials, and their electronic property significantly relies on the inter‐layer coupling. A certain setting of the inter‐layer coupling or stacking order in such materials may emerge exotic physical properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28][29][30] To date, the band structures of the β-P, β-As, and β-Sb twisted systems have also been explored by density functional theory (DFT) methods. [31][32][33][34] An et al found that the flat bandwidth of 10 meV in β-Sb appeared at 6.01 ○ . 34 Agnihotri et al studied the evolution of interlayer coupling in twisted bilayers of β-P and β-As, resulting in significant changes in the bandgap.…”
mentioning
confidence: 99%
“…We can find that a, r, and h are in good agreement with the previous study. 31,33,49,50 However, the interlayer distance differs by ∼6%, 33,[50][51][52] which can be sourced from the different methods used to treat vdW interaction. In this study, the DFT-D3 method with Becke Jonson damping is used, which is distinguished from the previous study.…”
mentioning
confidence: 99%